Heterogeneous ideas production and endogenous growth: An empirical investigation - Kul B. Luintel; Mosahid Khan (Cardiff University, Cardiff Business School, 2008)
We examine the dynamics of ideas production and knowledge-productivity relationship in a panel of 19 OECD countries. A new data set of triadic patents is used. We rigorously address the issues of cross-country heterogeneity and endogeneity. Domestic and foreign ideas stocks exert positive but heterogeneous effects on ideas production. We find evidence of duplicate R&D but little support for endogenous growth. Countries with low domestic ideas bases could considerably improve productivity through ideas accumulation; however, this effect is modest for countries with sizeable ideas bases. An implication is that country-specific R&D policy appears potentially more effective than the one-size-fits-all approach.
Keywords: F12; F2; O3; O4; C15; 330; Knowledge Stocks; Dynamic Heterogeneity; TFP; Methods of Moments; Forschungs- und Technologiepolitik; Erfindung; Produktivität; Wirtschaftswachstum; OECD-Staaten